2011
DOI: 10.1002/cncr.26481
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment and routine echocardiogram monitoring during chemotherapy for anthracycline‐induced cardiotoxicity rarely identifies significant cardiac dysfunction or alters treatment decisions

Abstract: BACKGROUND:The widespread use of anthracycline chemotherapy has contributed to improved outcomes in children with cancer. The most feared complication of the anthracyclines is cardiotoxicity. Routine echocardiographic monitoring typically is used before, during, and after treatment to minimize cardiotoxicity. The ideal use of screening before and during chemotherapy remains uncertain. METHODS: This was a retrospective review of children who were treated at a single cancer treatment center over 5 years. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…Although the vast majority (92.7%) of the 5,057 patients receiving anthracyclines in the study underwent a baseline evaluation of cardiac function, 2 recent retrospective studies 5,6 have questioned the utility of cardiac evaluation in patients treated with anthracyclines. The study by Watts et al 6 was designed in children, who have less cardiovascular risk factors than adults and a lower occurrence of impaired baseline LVEF.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the vast majority (92.7%) of the 5,057 patients receiving anthracyclines in the study underwent a baseline evaluation of cardiac function, 2 recent retrospective studies 5,6 have questioned the utility of cardiac evaluation in patients treated with anthracyclines. The study by Watts et al 6 was designed in children, who have less cardiovascular risk factors than adults and a lower occurrence of impaired baseline LVEF.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, 2 recent retrospective studies have questioned the utility of measuring a baseline LVEF in all patients. 5,6 Finally, whether other echocardiographically derived measures, such as LV size, are useful in the prediction of symptomatic HF in patients treated with anthracyclines is unknown. The objectives of the present study were twofold: (1) to detail the occurrence of and risk factors for symptomatic HF and cardiac death (major cardiac events) in a large contemporaneous population of patients treated with anthracyclines and (2) to evaluate the role of echocardiographically derived LVEF and LV dimensions measured before chemotherapy in the prediction of symptomatic HF and cardiac death in patients treated with anthracyclines.…”
mentioning
confidence: 99%
“…In a clinical trial involving 944 early breast cancer patients with LVEF ≥ 50% by MUGA prior to treatment with doxorubicin-cyclophosphamide-paclitaxel-trastuzumab, LVEF independently predicted cardiac events (HF [36 patients], cardiac death [one patient]) over 7 years follow-up when prechemotherapy LVEF was <55% (i.e., 50-54%) [42]. The predictive utility of LVEF was less apparent among pediatric cancer patients in a retrospective study of 356 children followed over 5 years for possible anthracycline-induced cardiac damage which found that LVEF assessments by 2DE before and during chemotherapy detected only one patient with symptomatic HF and did not future science group www.futuremedicine.com impact treatment decisions [62]. Data addressing the utility of systematic follow-up LVEF assessments in adult cancer survivors with a history of cytotoxic therapy are lacking [63].…”
Section: Resting Left Ventricular Ejection Fractionmentioning
confidence: 99%
“…(29) Beyond the points raised, the merit of routine screening protocols of the cardiac function of cancer patients has been questioned in general. (32) The current Children’s Oncology Group guidelines, largely endorsed in the recent expert consensus statement by the American Heart Association, recommend echocardiographic surveillance intervals based on cumulative anthracycline dose and radiation exposure. (33) For those 50% of survivors deemed to be at high risk of cardiovascular complications (>300 g/m2 doxorubicin equivalent dose of anthracyclines with or without radiation), yearly echocardiograms are recommended.…”
Section: Cardiotoxicitymentioning
confidence: 99%